Az érték a marketingben - Rekettye, Gábor (Marketing & Menedzsment, 2017)
The original study published in the Hungarian Journal of Marketing & Management was the summary of the dissertation submitted to the Hungarian Academy of Sciences for receiving the scientific title Doctor of the Academy of Sciences. This kind of dissertation required from the candidate to summarize the main achievements of his scientific carrier. The saying of the dissertation was organized around the notion of value. The three main parts of the thesis were the following: (1) market orientation as the prerequisite of value creation, (2) value creation and value management in the organizations and (3) value subtraction i.e. pricing. After 15 years, the author puts two questions: firstly, whether he is still satisfied with the quality of his original work and secondly whether the findings he wrote at that time are still valid or not. His answer to the first question is a definite yes while the answer to the second is more sophisticated. Due to the turbulent times of the 21s' century some of his statements are even more valid than at that time, some however would need certain rethinking.